Identification of unmet information needs among families of critically ill patients and their association with post-intensive care syndrome-family: protocol for a single-center cross-sectional study - Yoshiyasu Ito; Takuro Hamaguchi; Masatomo Suzuki; Yasushi Otaka; Mariko Asai; Yukihiro Sakaguchi; Yuki Shirai; Eisho Yoshikawa; Amane Tateno; Shoji Yokobori (BMC Palliative Care)
Abstract Background Families of critically ill patients in the intensive care unit (ICU) need a variety of information about the patient. Meeting these information needs improves the quality of communication between the family and ICU staff, as well as reduces the risk of post-intensive care syndrome-family (PICS-F). However, information needs continue to be unmet, and information regarding which specific information needs are met or unmet is insufficient. Additionally, the unmet needs that affect PICS-F are unknown. Therefore, this study aims to identify the unmet information needs of families of patients admitted to the ICU in terms of communication with ICU staff and determine their association with PICS-F. Methods This study will be a single-center cross-sectional study using a questionnaire survey. The participants will include family members of patients admitted to the emergency ICU of the Department of Emergency and Critical Care Medicine, Nippon Medical School Hospital in Japan. Eligibility for participation will be assessed from medical records, and family members of patients who meet the eligibility criteria will be identified and sent a questionnaire. PICS-F and unmet information needs will be assessed 1 to 12 months after patients leave the ICU. PICS-F assessment will include the evaluation of anxiety, depression, post-traumatic stress disorder, and prolonged grief disorder. Univariate and multiple logistic regression analyses will be used to examine the association between PICS-F and unmet information needs. Discussion This study will fill a research gap in communication between ICU staff and families of ICU patients by examining the information that tends not to be provided or understood by families, thereby providing an understanding of the information that is likely to be an unmet information need. Additionally, this study can contribute to the development of future communication strategies by investigating which unmet information needs are associated with PICS-F risk, thus emphasizing the information needs that should be given priority when developing effective communication strategies. Trial registration University Hospital Medical Information Network Center Clinical Trials Registry UMIN 000053813.